2013
DOI: 10.1155/2013/196704
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Hepatitis B Vaccination in Cirrhosis of Liver

Abstract: Introduction. Patients with chronic liver disease (CLD) are more likely to have severe morbidity and fatality rate due to superimposed acute or chronic hepatitis B (HBV) infection. The literature has shown that hepatitis B vaccines are safe and effective in patients with CLD, but the data in cirrhosis liver is lacking. We assessed the safety and immunogenicity of HBV vaccine in patients with cirrhosis liver. Methods. CTP classes A and B CLD patients negative for hepatitis B surface antigen and antibody to hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 15 publications
(10 reference statements)
1
51
1
1
Order By: Relevance
“…HBV infection in cirrhotic patients may have serious consequences as the clinical phenotype of the disease is much more severe because of the impaired functional capacity of the liver compared to the acute HBV infection in healthy individuals. However, several studies have shown that the immunogenicity following HBV vaccination in patients with liver cirrhosis seem to be ineffective . It has been shown that administration of additional vaccine doses after a primary vaccination series in subjects who do not respond to the vaccination is not associated with the development of adverse events …”
Section: Vaccination Schedulesmentioning
confidence: 99%
See 2 more Smart Citations
“…HBV infection in cirrhotic patients may have serious consequences as the clinical phenotype of the disease is much more severe because of the impaired functional capacity of the liver compared to the acute HBV infection in healthy individuals. However, several studies have shown that the immunogenicity following HBV vaccination in patients with liver cirrhosis seem to be ineffective . It has been shown that administration of additional vaccine doses after a primary vaccination series in subjects who do not respond to the vaccination is not associated with the development of adverse events …”
Section: Vaccination Schedulesmentioning
confidence: 99%
“…However, the efficacy of the HBV vaccine immunization depends on various factors such as increasing age, obesity, and existence of underlying diseases . Attempts to immunize patients with liver cirrhosis with the standard dose have been proven relatively ineffective . The seroconversion rates and antibody titers among these patients have been shown to be much lower compared to healthy individuals .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were insufficient clinical data to determine whether any of those with positive HBcAb status had taken up vaccination which was subsequently unsuccessful, with or without the influence of advanced liver disease. However, rates of vaccine efficacy are almost 90% in those with compensated cirrhosis and higher in those without significant liver disease . Given the low rates of vaccine uptake in PWID population, it is improbable that the association between HBcAb and cirrhosis is due to vaccine nonresponse, and then, subsequent infection with HBV is already in cirrhotic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many providers use only the double dose vaccine with either three or four injections [58]. Although some protection from HBV vaccine exists even when anti-HBsAb titers drop below 10 mIU/mL, data in other immunocompromised hosts (for example end-stage liver disease) suggests that there is benefit from boosting HBV immunity when anti-HBsAb titers fall <10 IU/mL [59].…”
Section: Hbv Vaccinationmentioning
confidence: 99%